Bile Sensing: The Activation of Vibrio parahaemolyticus Virulence - Letchumanan, Vengadesh; Chan, Kok-Gan; Khan, Tahir M.; Bukhari, Sarah I.; Ab Mutalib, Nurul-Syakima; Goh, Bey-Hing; Lee, Learn-Han (Frontiers in Microbiology, 2017)
Bacteria must develop resistance to various inhospitable conditions in order to survive in the human gastrointestinal tract. Bile, which is secreted by the liver, and plays an important role in food digestion also has antimicrobial properties and is able to disrupt cellular homeostasis. Paradoxically, although bile is one of the guts defenses, many studies have reported that bacteria such as Vibrio parahaemolyticus can sense bile and use its presence as an environmental cue to upregulate virulence genes during infection. This article aims to discuss how bile is detected by Vibrio parahaemolyticus and its role in regulating type III secretion system 2 leading to human infection. This bile-bacteria interaction pathway gives us a clearer understanding of the biochemical and structural analysis of the bacterial receptors involved in mediating a response to bile salts which appear to be a significant environmental cue during initiation of an infection.